(2 + cos^2 x)(1+ tan^2 x)
= 2 + 2tan^2x + cos^2x + cos^2x*tan^2x
= 2 + 2tan^2x + cos^2x (1 + tan^2x)
= 2 + 2tan^2x + 1/sec^2x * sec^2x
= 2 + 2tan^2x + 1
= 3 + 2tan^2x
2007-02-05 07:02:27
·
answer #1
·
answered by Sachu 2
·
0⤊
0⤋
Substitute sinx / cos x for tan x to obtain: -
(2 + cos²x)(1 + sin²x/cos²x)
= 2 + 2 sin²x/cos² x + (cos²x + sin²x)
= 2 + 2 tan²x + 1
= 3 + 2 tan²x as required.
2007-02-05 09:32:14
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
multiply out
2+ 2tan^2 (x) + cos^2 (x) + sin^2(x)tan^2(x) = 3 + 2tan^2 (x)
Remember tan^2 (x) = sin^2 (x) / cos^2 (x)
Insert for tan^2 (x)
2+ 2tan^2 (x) + cos^2 (x) + sin^2(x)(sin^2 (x) / cos^2 (x)) = 3 + 2tan^2 (x) = 3 + 2tan^2
2+ 2tan^2 (x) + cos^2 (x) + sin^2(x) = 3 + 2tan^2
Remember sin^2 (x) + cos^2 (x) = 1
2+ 2tan^2 (x) + 1 = 3 + 2tan^2
QED
2007-02-05 07:08:48
·
answer #3
·
answered by jbjt05 2
·
0⤊
0⤋
The cost of tan is free in a hot country. But in a cold country, the cost of tan is 3 x the number of times in the tanning salon.
2007-02-09 05:46:44
·
answer #4
·
answered by Dingbat O'Giddy 2
·
0⤊
0⤋
LHS=
(2 + cos^2 X)(1+ tan^2 X)
=2+(cosX)^2+2(tanX)^2
+(cosX)^2*(tanX)
{multiplying out}
=2+(cosX)^2+2(tanX)^2
+(cosX)^2*(sinX)^2/(cosX)^2
{tanX=sinX/cosX}
=2+[(cosX)^2+(sinX)^2]
+2(tanX)^2
=2+1+2(tanX)^2{pythagoras}
=3+2(tanX)^2
=RHS
therefore,
(2 + cos^2 X)(1+ tan^2 X)
= 3 + 2tan^2 X
i hope that this helps
2007-02-05 22:29:22
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
I hope I'm not doing someone's homework! 2(x+3)=x+7 2x+6=x+7 (multiply 2 by the equation in brackets) 2x+6-x=7 (move the x's to one side) 2x-x=7-6 (move the numbers to the other) x=1 (do the equation on each side)
2016-05-24 18:54:41
·
answer #6
·
answered by ? 4
·
0⤊
0⤋
(2+cos^2x)(1+tan^2x) (( 1+tan^2x=1/cos^2x))
=(2+cos^2x)(1/cos^2x)
=2/cos^2x+1
=2(1+tan^2x)+1
=2+2tan^2x+1=3+2tan^2x
2007-02-05 07:00:48
·
answer #7
·
answered by Esmaeil H 2
·
0⤊
0⤋
(2+cos^2X)(1+tan^2X)
=2+cos^2X+2tan^2X+cos^2X*tan^2X
but
tan^2X=sin^2X/cos^2X
thus
=2+cos^2X+2tan^2X+sin^2X
and we know that
cos^2X+sin^2X=1
thus the final equation is
2+1+2tan^2X=3+2tan^2X
2007-02-06 05:20:03
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
open university?
2007-02-05 06:50:04
·
answer #9
·
answered by steven e 7
·
0⤊
0⤋
http://www.endofworld.net/
2007-02-05 06:49:31
·
answer #10
·
answered by bluebird 2
·
0⤊
0⤋